Prevalência da Síndrome Metabólica em uma População Ribeirinha do Pantanal Sul-Mato-Grossense e Fatores de Risco para Doença Cardiovascular - Zanre, Renato Ferreira De Almeida (2021)
Primary health care (PHC) is of fundamental importance when it comes to public health and has the greatest health applicability in the Family Health Strategy (FHS). However, it is known that SUS has not yet achieved complete success in trying to meet the health needs of families living in rural areas. The study population, the riverside community of Passo do Lontra, is one of those rural populations that has difficulty accessing health services. This population has unhealthy lifestyle habits, which makes it predisposing to the development of metabolic disorders. Metabolic Syndrome (MetS) is characterized by a set of pathophysiological abnormalities associated with Cardiovascular Diseases (CVD). The appearance of MS has a multifactorial nature, with aspects related to genetic and environmental factors, such as habits related to lifestyle, physical activity and food routine. The study population, the riverside community of Passo do Lontra, has unhealthy lifestyle habits. The objective of this study was to evaluate the prevalence of MS and risk factors for CVD in this population through a crosssectional retrospective epidemiological analysis of the care provided by the Base of Studies of the Pantanal of UFMS during the years 2010 to 2016. The results showed that this population has a prevalence of MS of 42%, this value is considered high and higher than the national average. It was also demonstrated that the presence of MS in this population was associated with the presence of other metabolic dysfunctionalities, such as increased uric acid, BMI and non-HDL cholesterol. It is essential that the data obtained in this work guide public policies through measures to promote PHC in this population. Awareness measures, guidance on physical activity practices and a balanced diet are fundamental implementations for the reversal of this situation in this population.